Wage Bargining with Time-Varying Threats - Cramton, Peter C.; Tracy, Joseph S. (Journal of Labor Economics, 1994)
We study wage bargaining in which the union is uncertain about the firm's willingness to pay and threat payoffs vary over time. Strike payoffs change as replacement workers are hired, as strikers find temporary jobs, and as inventories or strike funds run out. We find that bargaining outcomes are substantially altered if threat payoffs vary. If dispute costs increase in the long run, then dispute durations are longer, settlement rates are lower, and wages decline more slowly during the short run (and may even increase). The settlement wage is largely determined from the long-run threat, rather than the short-run threat.